An Update on Developments in Female Hormonal Contraception - A. Garside, Deborah; Gebril, Ayman; Nimmo, Natalie; Alsaadi, Manal; B. Mullen, Alexander; A. Ferro, Valerie (Current Women's Health Reviews, 2012)
The human population continues to grow in some parts of the world, which has severe impact on resources, health and the environment. Individually, contraception enables women to choose their optimal family size and birth spacing, while in resource-poor countries it can help lift families out of poverty. While the oral contraceptive pill revolutionised female contraceptive options, there was a price to pay in terms of increased health risks. Today, improved formulations have been developed, together with non-oral hormonal technologies. This review will examine the history of female contraceptive research and provide an update on the status and future direction of new products.
Keywords: oestrogen